Potensi Pemanfaatan Koleksi Filologi di Museum Provinsi Sulawesi Tenggara sebagai Sumber Belajar Sejarah Lokal pada Jenjang SMA - Harnisa, Susi; Urlialy, Gesia Mira; Pusparani, Rina (Jambura History and Culture Journal, 2025)
This study aims to describe the potential of the philological collection at the Southeast Sulawesi Provincial Museum as a learning resource for history education at the high school level and to explain strategies for its utilization in history learning based on the 2013 Curriculum. This research uses a descriptive qualitative approach with data collection techniques including observation interviews and documentation and data analysis following the Miles and Huberman model. Data validity was ensured through source triangulation. The findings indicate that the museum’s philological collection such as the fifteenth-century daluang Qur’an manuscript and the historical manuscript of the Buton Kingdom holds significant historical and cultural value and aligns with the core competencies in the curriculum. Its implementation in learning through a Project Based Learning model fosters students’ historical thinking and character development. These findings contribute academically to the development of manuscript-based local history learning resources and carry practical implications for cultural preservation through education. These results highlight the importance of integrating philological collections as educational tools that support the implementation of the 2013 Curriculum based on local wisdom.